2020
DOI: 10.1371/journal.pone.0243054
|View full text |Cite
|
Sign up to set email alerts
|

Does cotrimoxazole prophylaxis in HIV patients increase the drug resistance of pneumococci? A comparative cross-sectional study in southern Ethiopia

Abstract: Background Infections caused by antibiotic-resistant bacteria results in high rates of morbidity and mortality. Although the prolonged cotrimoxazole (CTX) prophylaxis is arguably associated with the risk of increasing drug resistance in the common pathogens, information regarding its impact on Streptococci pneumoniae / pneumococcus is very limited. Objective This study was conducted to investigate the effect of cotrimoxazole prophylaxis on nasopharyngeal colonization rate and antimicrobial resistance using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In Malawi, as part of standard HIV clinical management, PLHIV are put on daily co-trimoxazole prophylaxis 17, 18 . Consistent with purifying selection and in agreement with previous studies 44, 45 , there was higher prevalence of co-trimoxazole resistant carriage isolates in PLHIV than HIV-uninfected participants. Considering that co-trimoxazole is a broad-spectrum antimicrobial and its resistance is associated with penicillin resistance 45, 46 , it could differentially alter the microbiota in the oropharyngeal and nasopharyngeal compartments, resulting in stronger selection for multi-drug resistant pneumococci.…”
Section: Discussionsupporting
confidence: 91%
“…In Malawi, as part of standard HIV clinical management, PLHIV are put on daily co-trimoxazole prophylaxis 17, 18 . Consistent with purifying selection and in agreement with previous studies 44, 45 , there was higher prevalence of co-trimoxazole resistant carriage isolates in PLHIV than HIV-uninfected participants. Considering that co-trimoxazole is a broad-spectrum antimicrobial and its resistance is associated with penicillin resistance 45, 46 , it could differentially alter the microbiota in the oropharyngeal and nasopharyngeal compartments, resulting in stronger selection for multi-drug resistant pneumococci.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 399 children below five years of age were enrolled with a median [interquartile range [IQR] age of 19 [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ] months and 212 (53%) were males. The gender distribution was almost equal between two groups ( p = 0.463).…”
Section: Resultsmentioning
confidence: 99%
“…HIV infection has been reported to be a risk factor for colonization with MDR pathogens [ 12 ]; this has partly been attributed to trimethoprim/sulfamethoxazole prophylaxis that is routinely given to prevent opportunistic infections [ 13 , 14 ]. The high prevalence of HIV and the emergence of MDR complicate efforts to control bacterial infections in many LMIC settings.…”
Section: Introductionmentioning
confidence: 99%
“… 48 The use of co-trimoxazole for prophylaxis of opportunistic infections in people living with HIV (PLWHIV) might also promote selective pressure, hence the high levels of resistance noted. 49 A study in southern Ethiopia revealed that co-trimoxazole prophylaxis increased the risk of resistance to co-trimoxazole, and this was statistically associated with co-resistance to penicillin. 49 …”
Section: Discussionmentioning
confidence: 99%
“… 49 A study in southern Ethiopia revealed that co-trimoxazole prophylaxis increased the risk of resistance to co-trimoxazole, and this was statistically associated with co-resistance to penicillin. 49 …”
Section: Discussionmentioning
confidence: 99%